Improvement Ability Students' Science Literacy in Aspects Knowledge and Competence Using the PBL Model - Ramadi Ramadi; Wahyuni Satria Dewi; Yenni Darvina Yenni; Fuja Novitra Fuja (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
Scientific Literacy is important in improving physics learning outcomes. looking at the situation in the field, student scientific literacy abbilities are still very low. The learningcarried out by students has mot simulated aspects of scientific literacy. the solutions given is to apply the PBL model. This research aims to find out whether there is an increase in students scientific literacy skill before and after carrying out learning using the PBL model. This research is a quantitative research with a pretest-posttest control group design. The population of this study was class X SMAN 1 Sungai Limau. The sampel is class X.3. the research Instruments used are teaching modules and stientific literacy tests. The data analysis techniques used are descriptive analisis techniques, normality tests, and hypothesis test. Based on the result of research hypothesis testing on students’ scientific literacy abilities, a significance value of 0.000000004 was obtained at a significance value at significance 0.05. Therefore, is accepted and is rejected. This means that there is an increase in scientific literacy abilities in the knowledge aspect and competency aspect after using the PBL model in class X at SMAN 1 Sungai Limau